Patient Decision Control and the Use of Cardiac Catheterization. Issue 4 (July 2015) - Mitchell, Suzanne E.; Paasche-Orlow, Michael K.; Orner, Michelle B.; Stewart, Sabrina K.; Kressin, Nancy R.
Background: Shared decision-making is a key determinant of patient-centered care. A lack of patient involvement in treatment decisions may explain persistent racial disparities in rates of cardiac catheterization (CCATH). To date, limited evidence exists to demonstrate whether patients who engage in shared decision-makingare more or less likely to undergo non-emergency CCATH. Objective: To assess the relationship between participation in the decision to undergo a CCATH and the use of CCATH. We also examined whether preference for or actual engagement in decision-making varied by patient race. Methods: We analyzed data from 826 male Veterans Administration patients for whom CCATH was indicated and who participated in the Cardiac Decision Making Study. Results: After controlling for con-founders, patients reporting any degree of decision control were more likely to receive CCATH compared with those reporting no control (doctor made decision without patient input) (54% vs 39%, P<.0001). Across racial groups, patients were equally likely to report a preference for control over decision-making (P=.53) as well as to experience discordance between their preference for control and their perception of the actual decision-making process (P=.59). Therefore, these factors did not mediate racial disparities in rates of CCATH use. Conclusion: Shared decision-making is an essential feature of whole-person care. While participation in decision-making may not explain disparities in CCATH rates, further work is required to identify strategies to improve congruence between patients' desire for and actual control over decision-making to actualize patient-centered care.